1974
DOI: 10.1071/bi9740591
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Monotreme Proteins. V. Amino Acid Sequence of the a-Chain of Haemoglobin From the Platypus, Ornithorhynchus anatinus

Abstract: Blood from the platypus contained three haemoglobins which were separated by chromatography on DEAE-Sephadex. The major component, Hb-I, was converted to globin and fractionated into the oc-and p-chains by chromatography on eM-cellulose in 8M urea-thiol buffers, and the complete amino acid sequence of the 141 residues of the oc-chain were determined. Peptides derived from the oc-chain by tryptic digestion were isolated by paper ionophoresis and chromatography. The amino acid sequences were determined by the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…[6][7][8][9] In this set of 35 alpha sequencies, two actual GDs are required, one for the two echidna chains (ECH IB and IIA) and another for the two chicken chains (CHI All and Al). These real GDs are desig- The ordinate scale in millions of years is inferred from fossil evidence on ancestral splitting times of the species from which the sequences come.…”
Section: Tree Construction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] In this set of 35 alpha sequencies, two actual GDs are required, one for the two echidna chains (ECH IB and IIA) and another for the two chicken chains (CHI All and Al). These real GDs are desig- The ordinate scale in millions of years is inferred from fossil evidence on ancestral splitting times of the species from which the sequences come.…”
Section: Tree Construction Resultsmentioning
confidence: 99%
“…Since the duplication giving rise to these two chains is placed in the species lineage to echidna after this lineage separates from that to platypus (Figs. [6][7][8][9], there is no need to postulate any ensuing GE events.…”
Section: Gene Expression Eventsmentioning
confidence: 99%
“…The substitutions at the oc 1 ,81 contacts and at the internal positions appear Table 3. Significant amino acid differences in echidna and platypus haemoglobins Sequence data are from Whittaker et al (1972Whittaker et al ( , 1973, and Whittaker and Thompson (1974). The functional significance is from Goodman et al (1975) to have sufficiently similar stereochemical properties that they are unlikely to have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to understand the phylogenetic relationships of the monotremes the amino acid sequences of the f3-chain (Whittaker et al 1972) and IX-chain (Whittaker et al 1973) of echidna haemoglobin IB were determined as well as the sequences of the IX-chain (Whittaker and Thompson 1974) and f3-chain (Whittaker and Thompson 1975) of platypus haemoglobin. Calculations based on the differences in amino acid sequence of the IX-chain suggested that monotremes diverged from other mammalian groups 211 million years ago, while calculations based on the f3-chain gave 132 million years for the divergence date.…”
Section: Introductionmentioning
confidence: 99%
“…Citraconylation followed by tryptic digestion and fractionation on DEAE-cellulose was done as previously described (Whittaker and Thompson 1974) using 200 mg of carboxymethylated myoglobin. Samples of each fraction (25,u1 made to 0·5 ml with water) were taken for radioactive counting with 5 ml of the mixture of Butler (1961).…”
Section: Citraconylation Of S-carboxymethylated Myoglobinmentioning
confidence: 99%